The implementation of multiliteracy based pjbl to improve innovation and creativity skill - Hanifah, Desty Putri (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
This study aims to determine the improvement of students' ability to innovate and creativity through the application of multiliteracy-based PjBL. The type of research used is Classroom Action Research (PTK) model Kemmis and Mc. Taggart model with the research subject being second semester students of the PGMI study program at the Al-Qur'an University of Science in 2022/2023. The research instruments used were performance tests, observation sheets, questionnaires, and field notes. The results of the performance test show that multiliteracy-based PjBL can increase the ability to innovate by 7.88% and creativity by 6.88%. Students' innovation and creativity were realized in several products that were exhibited in the work title, including renn car, Nusantara quartet, blog, dance creation, vlog of historical places, and so on. The average score of improvement in the ability to innovate between cycles is 1.26 and creativity is 1.65. In addition to improving the ability to innovate and creativity, questionnaire data shows that student enthusiasm in attending lectures has also increased. As many as 58% of students felt enthusiastic during the lecture by applying multiliteration-based PjBL. Based on the results of observations and field notes, intensive guidance during project work is very helpful for students in expressing ideas and more creative problem solving. The integration of PjBL syntax and literacy elements can stimulate students to think divergently while improving their ability to present their work attractively. This study aims to determine the improvement of students' ability to innovate and creativity through the application of multiliteracy-based PjBL. The type of research used is Classroom Action Research (PTK) model Kemmis and Mc. Taggart model with the research subject being second semester students of the PGMI study program at the Al-Qur'an University of Science in 2022/2023. The research instruments used were performance tests, observation sheets, questionnaires, and field notes. The results of the performance test show that multiliteracy-based PjBL can increase the ability to innovate by 7.88% and creativity by 6.88%. Students' innovation and creativity were realized in several products that were exhibited in the work title, including renn car, Nusantara quartet, blog, dance creation, vlog of historical places, and so on. The average score of improvement in the ability to innovate between cycles is 1.26 and creativity is 1.65. In addition to improving the ability to innovate and creativity, questionnaire data shows that student enthusiasm in attending lectures has also increased. As many as 58% of students felt enthusiastic during the lecture by applying multiliteration-based PjBL. Based on the results of observations and field notes, intensive guidance during project work is very helpful for students in expressing ideas and more creative problem solving. The integration of PjBL syntax and literacy elements can stimulate students to think divergently while improving their ability to present their work attractively.